In Situ Transesterification of Microbial Biomass for Biolubricant Production Catalyzed by Heteropolyacid Supported on Niobium - Zorn, Savienne M. F. E.; da Silva, Ana Paula T.; Bredda, Eduardo H. [UNESP]; Bento, Heitor B. S. [UNESP]; Pedro, Guilherme A.; Carvalho, Ana Karine F.; Silva, Messias Borges [UNESP]; Da Rós, Patrícia C. M. (My University, 2022)
Lubricants are substances of the foremost importance in the modern world, as they are essential to the proper functioning of various mechanisms. Most lubricants, however, are still made from petroleum fractions. I light of this, and due to various environmental problems, the search for feasible biolubricants has become essential. This study obtained biolubricants through the in situ transesterification of microbial biomass, containing at least 20 wt% of lipids. The following two distinct biomasses were evaluated: the marine microalgae, Dunaliella salina, and the consortium of microalgae-fungi, Scenedesmus obliquus and Mucor circinelloides. Microbial oil from both biomasses presented a fatty acid profile with high amounts of oleic acid. The oil of D. salina had a lower content of polyunsaturated fatty acids relative to the microbial consortium profile, which indicates that this is a good configuration for increasing biolubricant oxidation resistance. The catalyst used was a Keggin-structure heteropolyacid supported on niobium, H3 PMo12 O40 /Nb2 O5, activated at 150◦ C, which had high transesterification yields, notwithstanding the feedstocks, which were rich in free fatty acids. The performed transesterification reactions resulted in excellent yields, up to 97.58% and 96.80%, for marine microalgae and the consortium, respectively, after 6 h at 250◦ C, with 10 wt% of catalyst (related to the lipid amount). As such, the (H3 PMo12 O40 /Nb2 O5 ) catalyst could become an attractive option for producing biolubricants from microbial biomass.
Keywords: Biolubricant; Consortium; Dunaliella salina; Fusel oil; H3 PMo12 O40; Microalgae; Microbial biomass; Mucor circinelloides; Scenedesmus obliquus